PENGARUH EFIKASI DIRI TERHADAP KECEMASAN ATLET DALAM MENGHADAPI PERLOMBAAN PADA PERGURUAN PENCAK SILAT SATRIA AGUNG - Nasichuddin, Mohammad; Wardianto, Muhammad (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to examine the effect of self-efficacy on athletes’ anxiety in facing competitions at the Satria Agung Pencak Silat Academy. The research employed a quantitative approach with a correlational design. The subjects were 141 athletes selected using simple random sampling. The instruments applied were the self-efficacy scale and the anxiety scale. The findings revealed that self-efficacy significantly influences athletes’ anxiety. Athletes with high self-efficacy tend to manage emotions effectively, display stronger confidence, and experience lower anxiety. Conversely, athletes with low self-efficacy are more vulnerable to anxiety, which may hinder their performance during competitions. These results highlight the importance of psychological development, particularly enhancing self-efficacy, as a strategy to reduce competitive anxiety and support athletes in achieving optimal performance.